DISPRAXIA EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA CAP. GEOVANNI CALLES LASCANO COMUNIDAD JATARI CAMPESINO, PARROQUIA CALPI, CANTÓN RIOBAMBA, PERÍODO ABRIL –JULIO 2019 - Ashqui Morocho, Gino Ruben (2020)
This research work proposed to determine the levels of dyspraxia with respect to the development of motor coordination and locomotion of the students of the Educational Unit “Cap. Geovanni Calles Lascano ”, Parroquia Calpi, Riobamba, academic period April - July 2019, a methodology with a non-experimental type was used, for the type was descriptive, transversal, basic and field, the study population was the children of the Educational Unit “Cap. Geovanni Calles Lascano ”, whose sample was not probabilistic and intentional when working with 50 students from initial I and II, including 24 boys and 26 girls; The psychometric test applied technique, the Psychomotor Assessment Scale instrument in preschool, which facilitated the analysis and interpretation of the results, concluding that it has been established that the level of dyspraxia with respect to motor coordination of the students are at a medium level, with respect to locomotion, the middle level predominates because the infants have difficulties walking in a straight line, however, in relation to the comparisons between boys and girls it was evident that the children they have a better management with respect to the development of coordination.